Antistatic flame-retardant ultra-high molecular weight polyethylene fiber and preparation method thereof
By combining ultra-high molecular weight polyethylene with modified montmorillonite clay and silica nanoparticles, the method enhances anti-static and flame-retardant properties in UHMWPE fibers, forming a nanocomposite structure that disperses charge and inhibits combustion.
Patent Information
- Application Number
- CN202510558461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-07-15
AI Technical Summary
In the prior art, it is difficult to achieve good antistatic properties and flame retardant properties in ultra-high molecular weight polyethylene fibers without adding graphene materials.
By selecting ultra-high molecular weight polyethylene and high-density polyethylene composites and adding functional components such as cationic montmorillonite and silica, anti-static flame-retardant ultra-high molecular weight polyethylene fibers are prepared, and nanonetwork structures are constructed using cationic montmorillonite and anionic silica composite materials to form conductive channels and fire-resistant barriers, and anti-static and flame-retardant properties are improved.
Without adding graphene material, good anti-static and flame retardant properties of ultra-high molecular weight polyethylene fibers are achieved. The composite fire-retardant barrier formed by the nano-layered structure of montmorillonite and the dense silicate layer of silica can be effectively improved.
Smart Images

Figure BDA0005383979750000141 
Figure BDA0005383979750000151
Abstract
Description
Technical Field
[0001] The present invention belongs to fiber composites, and particularly relates to an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene (UHMWPE) is one of the world's three major high-performance fibers and has great application prospects in the fields of national defense and military industry, aerospace, ocean engineering, and civil industry. UHMWPE fiber is a flexible chain macromolecule mainly connected by methylene groups. Since the chemical structure of the fiber macromolecule only contains some smaller side groups and end methyl groups and there are no polar bonds, methylene groups are easily stacked into the macromolecular lattice. Therefore, it has good symmetry and regularity, and the internal rotation barrier of single bonds is relatively low, and a three-dimensional structure with an orderly arrangement can be formed. After ultra-high molecular weight polyethylene is highly stretched, the molecular chains are highly oriented and crystallized along the stretching direction. The unique molecular structure makes UHMWPE fiber have excellent mechanical properties and at the same time has characteristics such as anti-bending, wear resistance, anti-cutting, and light aging resistance.
[0003] Chinese Patent (publication number CN118461174B) discloses an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber and a preparation method thereof. In this invention, ultra-high molecular weight polyethylene, high-density polyethylene, modified graphene, compound antioxidant, lubricant, and compatibilizer are mixed and then added to a blender. After being stirred evenly, they are put into a twin-screw extruder for melt spinning and water bath cooling to obtain an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber; when used as a filler, modified graphene can endow polyethylene fiber with excellent antistatic and flame-retardant properties. However, this patented technology requires the addition of modified graphene to achieve. How to endow ultra-high molecular weight polyethylene fiber with good antistatic and flame-retardant properties without adding graphene materials has become a technical problem to be solved.
[0004] Therefore, there is an urgent need for an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber. By screening suitable nano-fillers and modifying the fillers, good antistatic and flame-retardant properties can be obtained without adding graphene materials. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber. By selecting ultra-high molecular weight polyethylene and high-density polyethylene for compounding and adding functional components such as cationic montmorillonite and silica, an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber is prepared, and good antistatic and flame-retardant properties can be obtained without adding graphene materials.
[0006] The technical solution of the present invention is as follows:
[0007] In the first aspect of the present invention, an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber is provided.
[0008] It comprises the following raw materials in parts by weight: 80 - 90 parts of polyethylene, 2 - 4 parts of cationic montmorillonite, 2 - 4 parts of silicon dioxide, 0.6 - 0.8 parts of antioxidant, 0.8 - 1.2 parts of lubricant, and 0.4 - 0.6 parts of compatibilizer.
[0009] The preparation method of the cationic montmorillonite comprises: taking 2 - 4 parts of sodium-based montmorillonite by weight, adding it into 40 - 50 parts of quaternary ammonium salt solution for cationic intercalation treatment to obtain cationic montmorillonite.
[0010] As a preferred scheme, the weight parts of the polyethylene in the present invention can be 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, etc.
[0011] As a preferred scheme, the weight parts of the cationic montmorillonite in the present invention can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, etc.
[0012] As a preferred scheme, the weight parts of the silicon dioxide in the present invention can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, etc.
[0013] As a preferred scheme, the weight parts of the antioxidant in the present invention can be 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts, 0.8 parts, etc.
[0014] As a preferred scheme, the weight parts of the lubricant in the present invention can be 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, etc.
[0015] As a preferred scheme, the weight parts of the compatibilizer in the present invention can be 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, etc.
[0016] As a preferred scheme, the weight parts of the sodium-based montmorillonite in the present invention can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, etc.
[0017] As a preferred scheme, the weight parts of the quaternary ammonium salt solution in the present invention can be 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, etc.
[0018] As a preferred solution, the preparation method of the quaternary ammonium salt solution includes: by weight, mixing 10-12 parts of thionyl chloride and 20-30 parts of dimethyl sulfoxide, then adding 8-10 parts of methacrylic acid, 20-30 parts of N,N-dimethylformamide and 40-50 parts of tetrahydrofuran for heating reaction, and then adding 6-8 parts of 2,4,6-tris(dimethylaminomethyl)phenol for esterification reaction to obtain an intermediate; subjecting 20-30 parts of the intermediate to acidification treatment, and then adding 16-20 parts of epichlorohydrin for constant temperature reaction to obtain the quaternary ammonium salt solution.
[0019] The synthetic monomers in the quaternary ammonium salt solution have 2,4,6-tris(dimethylaminomethyl)phenol as the main skeleton. Double bonds are introduced by the esterification of the product of thionyl chloride and methacrylic acid with the hydroxyl groups on the skeleton, and cationic quaternary ammonium salts are obtained by the combination of epichlorohydrin and the amino groups on the skeleton, thereby obtaining a cationic quaternary ammonium salt solution with a double bond structure.
[0020] As a preferred solution, the temperature of the heating reaction is 60-64°C and the time is 160-180 min.
[0021] As a preferred solution, the conditions for the esterification reaction include: adding 2-4 parts of ethylenediamine and reacting at 60-64°C for 160-180 min;
[0022] As a preferred solution, the conditions for the acidification treatment include: adding 20-30 parts of the intermediate and 6-8 parts of a hydrochloric acid solution with a mass concentration of 36-40% to 40-50 parts of absolute ethanol, and acidifying at 24-28°C for 20-30 min first.
[0023] As a preferred solution, the conditions for the constant temperature reaction include: adjusting the pH to 7.2-7.6 and carrying out the constant temperature reaction at 40-45°C for 8-10 h.
[0024] As a preferred solution, the conditions for the cation intercalation treatment include: stirring at 80-86°C for 24-30 h, filtering by suction, washing with water, drying, and grinding.
[0025] In the octahedron of alumina in sodium-based montmorillonite, some trivalent aluminum is easily isomorphously replaced by divalent magnesium, resulting in a negatively charged inner surface. The excess negative charge will adsorb cations through the interlayer to compensate. By soaking sodium-based montmorillonite in the quaternary ammonium salt solution for intercalation treatment, the cations of the quaternary ammonium salt are adsorbed. At the same time, since the synthesized quaternary ammonium salt has multiple cationic groups, cationic montmorillonite is formed.
[0026] As a preferred solution, the silica is an anionic silica composite material;
[0027] The preparation method of the anionic silica composite material includes: by weight, subjecting 4-8 parts of silica to surface modification, and then mixing it with 4-8 parts of terminal-alkynylated magnetite, 2-4 parts of sodium ascorbate, 12-16 parts of triethylamine, and 600-800 parts of N,N-dimethylformamide for click reaction to obtain a silica composite material; adding 4-8 parts of maleic anhydride to 40-50 parts of N,N-dimethylformamide, stirring well, and then adding 2-4 parts of the silica composite material for thermal reaction to obtain the anionic silica composite material.
[0028] As a preferred scheme, the conditions for the surface modification include: adding 4-8 parts of silica to 60-80 parts of toluene for ultrasonic dispersion, then adding 0.2-0.6 part of γ-glycidoxypropyltrimethoxysilane and reacting at 80-90 °C for 12-14 h, filtering, washing with toluene, and drying in vacuum; then adding it to a mixed solution of 40-50 parts of methanol and 10-12 parts of deionized water, adding 2-4 parts of sodium azide and 0.01-0.03 part of ammonium chloride, and reacting at 70-80 °C for 20-24 h, washing with water, and drying in vacuum.
[0029] As a preferred scheme, the preparation method of the terminal-alkynylated magnetite includes: ultrasonically dispersing 0.3-0.6 part of magnetite in 80-100 parts of deionized water to obtain a dispersion, ultrasonically dispersing 0.2-0.4 part of polyacrylic acid in 60-80 parts of deionized water, and then dropwise adding 80-100 parts of the dispersion for carboxyl modification to obtain carboxyl-modified magnetite; subjecting the carboxyl-modified magnetite to terminal alkynylation to obtain terminal-alkynylated magnetite.
[0030] As a preferred scheme, the conditions for the carboxyl modification include: first ultrasonically dispersing for 30-40 min, then rapidly stirring at 90-96 °C for 50-60 min, adjusting the pH to 3.6-3.8, filtering, washing with water, and freeze-drying.
[0031] As a preferred scheme, the conditions for the terminal alkynylation include: ultrasonically dispersing 2-4 parts of the carboxyl-modified magnetite in 500-600 parts of N,N-dimethylformamide, successively adding 1.2-1.4 parts of EDC·HCl, 0.6-0.8 part of N-hydroxysuccinimide, and 1-3 parts of propargylamine, stirring at room temperature overnight, washing with water, and freeze-drying.
[0032] As a preferred scheme, the conditions for the click reaction include: placing it in a nitrogen atmosphere, adding 0.02-0.04 part of copper sulfate pentahydrate and reacting at 40-46 °C for 24-30 h, washing, and drying.
[0033] As a preferred embodiment, the conditions for the thermal reaction include: placing it under a nitrogen atmosphere, stirring for 8 - 10 h at 100 - 120 °C, cooling to room temperature, dissolving it in chloroform, filtering, washing with acetone, and drying under vacuum.
[0034] In the present invention, silica is first surface - modified to introduce azide groups, and then magnetite is first carboxyl - modified and then terminal - alkynylated. Then, with the help of sodium ascorbate, copper sulfate pentahydrate, etc., the click reaction between terminal alkyne and azide is achieved to form a triazole ring structure, obtaining a silica composite material. Then, the hydroxyl groups on the surface of silica in the silica composite material are subjected to a thermal reaction with maleic anhydride to introduce double bonds and carboxyl groups on the surface of the silica composite material.
[0035] As a preferred embodiment, the polyethylene is ultra - high - molecular - weight polyethylene and high - density polyethylene;
[0036] As a preferred embodiment, the mass ratio of the ultra - high - molecular - weight polyethylene to the high - density polyethylene is (1 - 2):1;
[0037] As a preferred embodiment, the viscosity - average molecular weight of the ultra - high - molecular - weight polyethylene is 1,000,000 - 1,500,000.
[0038] In the present invention, by selecting ultra - high - molecular - weight polyethylene and high - density polyethylene for compounding, and at the same time controlling the viscosity - average molecular weight of the ultra - high - molecular - weight polyethylene, a good compounding effect is ensured, and the antistatic performance and flame - retardant performance of the ultra - high - molecular - weight polyethylene fiber are improved.
[0039] As a preferred embodiment, the antioxidant is selected from one or more of antioxidant 1010 or antioxidant 168;
[0040] As a preferred embodiment, the lubricant is selected from one or more of calcium stearate or N,N'-ethylenebisstearamide;
[0041] As a preferred embodiment, the compatibilizer is selected from one or more of DuPont E100, DuPont E226, and Arkema CA100.
[0042] In the second aspect of the present invention, a method for preparing an antistatic and flame - retardant ultra - high - molecular - weight polyethylene fiber is provided, including the following steps:
[0043] Mix 80 - 90 parts of polyethylene, 2 - 4 parts of cationic montmorillonite, 2 - 4 parts of silica, 0.6 - 0.8 parts of antioxidant, 0.8 - 1.2 parts of lubricant, and 0.4 - 0.6 parts of compatibilizer, add them to a blender, stir evenly, then put them into a twin - screw extruder, carry out melt spinning, and cool in a water bath to obtain the antistatic and flame - retardant ultra - high - molecular - weight polyethylene fiber.
[0044] As a preferred embodiment, the temperature of the melt spinning is 180 - 200 °C.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The present invention selects ultra-high molecular weight polyethylene with a viscosity-average molecular weight of 1,000,000 - 1,200,000, reduces the melt spinning temperature, and avoids the failure of the modified components caused by too high temperature; the double bonds of the anionic silica composite can polymerize with the double bonds in the cationic montmorillonite during the melt spinning process, and at the same time, the carboxyl groups on the surface of the silica composite belong to anions and can combine with the quaternary ammonium salts in the cationic montmorillonite, thereby constructing a network structure of nano-components. The weak conductive channels constructed by cations and anions cooperate with the electron conduction path provided by iron oxide, which can effectively improve the antistatic performance of the material; the nano-layered structure of montmorillonite and the dense silicate layer of silica can form a composite fire barrier, effectively insulating heat while diluting combustible gases, and the decomposition products of quaternary ammonium salts during combustion and the iron ions of iron oxide can together capture free radicals and terminate the chain combustion reaction, synergistically improving the flame retardant performance.
[0047] (2) After the layered structure of montmorillonite in the present invention is uniformly dispersed in the fiber, it forms a nano-dispersed network to promote charge dissipation; the cationic montmorillonite modified by quaternary ammonium salts contains cations between layers, which can provide a weakly ionized conductive channel and reduce the surface resistance. The nano-layered structure of montmorillonite forms a continuous "fire barrier" during combustion, delaying the transfer of heat and flame into the fiber interior. At the same time, the interlayer structure can adsorb and dilute combustible gases (such as ethylene and propylene), reducing the flame spread rate; the quaternary ammonium salts decompose during combustion and react with free radicals to terminate the chain combustion reaction, improving the flame retardant performance.
[0048] (3) Iron oxide in the anionic silica composite of the present invention can provide an electron conduction path, form a local conductive path in the composite material, reduce the surface resistance of the material, and promote the dissipation of static charges, thereby improving the antistatic performance. At high temperature, silica migrates to the surface of the material to form a dense silicate layer, reducing the thermal conductivity. The iron ions of iron oxide can both catalyze carbon formation to improve the graphitization degree of the carbon layer and capture hydroxyl free radicals to inhibit the chain combustion reaction. Detailed Embodiments
[0049] To facilitate the understanding of the present invention, the following examples are listed. Those skilled in the art should understand that the examples are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.
[0050] The sources of some components in the examples and comparative examples are as follows:
[0051] Ultra-high molecular weight polyethylene I, with the grade LL-GM-1080, having a viscosity-average molecular weight of 1 million to 1.2 million, was purchased from Shanghai Lianle Chemical Technology Co., Ltd.;
[0052] Ultra-high molecular weight polyethylene II, with the product number P77511, having a viscosity-average molecular weight of 4.5 million to 5 million, was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0053] High-density polyethylene, with the grade HD6070EA, having a viscosity-average molecular weight of 0.04 million to 0.3 million, was purchased from PetroChina Dushanzi Petrochemical Company;
[0054] Commercially available sodium montmorillonite, with the product number M916670, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0055] Commercially available silica, with the product number S433667, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0056] Antioxidant 1010, with the product number P136696, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0057] Antioxidant 168, with the product number T161948, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0058] Calcium stearate, with the CAS number 1592-23-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0059] N,N'-Ethylenebisstearamide, with the CAS number 110-30-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0060] Compatibilizer: DuPont E100 compatibilizer, purchased from DuPont; DuPont E226 compatibilizer, purchased from DuPont; Arkema CA100 compatibilizer, purchased from Arkema;
[0061] Thionyl chloride, with the CAS number 7719-09-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0062] Dimethyl sulfoxide, with the CAS number 67-68-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0063] Methacrylic acid, with the CAS number 79-41-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0064] N,N-Dimethylformamide, with the CAS number 68-12-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0065] Tetrahydrofuran, with the CAS number 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0066] 2,4,6-Tris(dimethylaminomethyl)phenol, CAS No. 90-72-2, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0067] Epichlorohydrin, CAS No. 106-89-8, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0068] Silica, product number S433667, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0069] γ-Glycidoxypropyltrimethoxysilane, CAS No. 2530-83-8, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0070] Sodium azide, CAS No. 26628-22-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0071] Ammonium chloride, CAS No. 12125-02-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0072] Iron oxide black, product number I400322, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0073] Polyacrylic acid, CAS No. 9003-01-4, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0074] EDC·HCl, product number E106172, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0075] N-Hydroxysuccinimide, CAS No. 6066-82-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0076] Propargylamine, CAS No. 2450-71-7, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0077] Copper(II) sulfate pentahydrate, CAS No. 23254-43-5, was purchased from Shanghai Macklin Biochemical Co., Ltd.;
[0078] Sodium ascorbate, CAS No. 134-03-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0079] Triethylamine, CAS No. 121-44-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0080] Maleic anhydride, CAS No. 108-31-6, was purchased from Shanghai Macklin Biochemical Co., Ltd.
[0081] Example 1
[0082] This embodiment provides a method for preparing an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber, comprising the following steps:
[0083] 90 parts of polyethylene (60 parts of ultra-high molecular weight polyethylene I and 30 parts of high-density polyethylene), 4 parts of cationic montmorillonite, 4 parts of anionic silica composite material, 0.8 part of antioxidant 1010, 1.2 parts of lubricant calcium stearate, and 0.6 part of compatibilizer DuPont E100 are mixed and then added to a blender. After stirring evenly, they are put into a twin-screw extruder for melt spinning (temperature: 200 °C), and water bath cooling is carried out to obtain the antistatic and flame-retardant ultra-high molecular weight polyethylene fiber.
[0084] Preparation of the cationic montmorillonite: By weight, 12 parts of thionyl chloride and 30 parts of dimethyl sulfoxide are mixed, and then 10 parts of methacrylic acid, 30 parts of N,N-dimethylformamide, and 50 parts of tetrahydrofuran are added for heating reaction (temperature: 64 °C, time: 160 min). Then 8 parts of 2,4,6-tris(dimethylaminomethyl)phenol and 4 parts of ethylenediamine are added, and the reaction is carried out at 64 °C for 160 min to obtain an intermediate. 30 parts of the intermediate and 8 parts of a hydrochloric acid solution with a mass concentration of 40% are added to 50 parts of absolute ethanol. First, acidification is carried out at 28 °C for 20 min, and then 20 parts of epichlorohydrin are added for a constant temperature reaction. The pH is adjusted to 7.6, and the constant temperature reaction is carried out at 45 °C for 8 h to obtain a quaternary ammonium salt solution. 4 parts of sodium montmorillonite are added to 50 parts of the quaternary ammonium salt solution for cationic intercalation treatment, and stirring is carried out at 86 °C for 24 h. Filtration, washing with water, drying, and grinding are carried out to obtain the cationic montmorillonite.
[0085] Preparation of the anionic silica composite material: (1) Ultrasonically disperse 0.6 part of iron tetroxide in 100 parts of deionized water to obtain a dispersion. Ultrasonically disperse 0.4 part of polyacrylic acid in 80 parts of deionized water, then add 100 parts of the dispersion for carboxyl modification. First, ultrasonically disperse for 40 min, then rapidly stir at 96 °C for 50 min, adjust the pH to 3.8, filter, wash with water, and freeze-dry to obtain carboxyl-modified iron tetroxide. Ultrasonically disperse 4 parts of the carboxyl-modified iron tetroxide in 600 parts of N,N-dimethylformamide, successively add 1.4 parts of EDC·HCl, 0.8 part of N-hydroxysuccinimide, and 3 parts of propargylamine, stir at room temperature overnight, wash with water, and freeze-dry to obtain end-group-alkynylated iron tetroxide. (2) Ultrasonically disperse 8 parts of silica in 80 parts of toluene, then add 0.6 part of γ-glycidoxypropyltrimethoxysilane and react at 90 °C for 12 h, filter by suction, wash with toluene, and dry in vacuo. Then add it to a mixed solution of 50 parts of methanol and 12 parts of deionized water, add 4 parts of sodium azide and 0.03 part of ammonium chloride, and react at 80 °C for 20 h, wash with water, and dry in vacuo. Then mix it with 8 parts of end-group-alkynylated iron tetroxide, 4 parts of sodium ascorbate, 16 parts of triethylamine, and 800 parts of N,N-dimethylformamide for click reaction, place it in a nitrogen atmosphere, add 0.04 part of copper sulfate pentahydrate, and react at 46 °C for 24 h, wash, and dry to obtain a silica composite material. Add 8 parts of maleic anhydride to 50 parts of N,N-dimethylformamide and stir well, then add 4 parts of the silica composite material for thermal reaction, place it in a nitrogen atmosphere, stir at 120 °C for 8 h, cool to room temperature, dissolve it in chloroform, filter, wash with acetone, and dry in vacuo to obtain the anionic silica composite material.
[0086] Example 2
[0087] This example provides a method for preparing antistatic and flame-retardant ultra-high molecular weight polyethylene fibers, which includes the following steps:
[0088] Add 80 parts of polyethylene (40 parts of ultra-high molecular weight polyethylene I and 40 parts of high-density polyethylene), 2 parts of cationic montmorillonite, 2 parts of the anionic silica composite material, 0.6 part of antioxidant 168, 0.8 part of lubricant N,N'-ethylenebisstearamide, and 0.4 part of compatibilizer DuPont E226 into a mixer, stir evenly, then put it into a twin-screw extruder for melt spinning (temperature is 180 °C), and cool in a water bath to obtain antistatic and flame-retardant ultra-high molecular weight polyethylene fibers.
[0089] Preparation of the cationic montmorillonite: by weight, 10 parts of thionyl chloride and 20 parts of dimethyl sulfoxide are mixed, then 8 parts of methacrylic acid, 20 parts of N,N-dimethylformamide and 40 parts of tetrahydrofuran are added to carry out heating reaction (temperature is 60° C., time is 180 minutes), then 6 parts of 2,4,6-tris(dimethylaminomethyl)phenol and 2 parts of ethylenediamine are added, and the reaction is carried out at 60° C. for 180 minutes to obtain an intermediate; 20 parts of the intermediate and 6 parts of 36% hydrochloric acid solution are added to 50 parts of anhydrous ethanol, first acidified at 24°C for 30 minutes, then 16 parts of epichlorohydrin are added for constant temperature reaction, the pH is adjusted to 7.2, and the reaction is carried out at a constant temperature of 40°C for 10 hours to obtain a quaternary ammonium salt solution; 2 parts of sodium montmorillonite are added to 40 parts of the quaternary ammonium salt solution for cationic intercalation treatment, stirred at 80°C for 30 hours, filtered, washed with water, dried, and ground to obtain cationic montmorillonite.
[0090] The preparation of the anionic silica composite material comprises the following steps: (1) ultrasonically dispersing 0.3 parts of ferroferric oxide in 80 parts of deionized water to obtain a dispersion, ultrasonically dispersing 0.2 parts of polyacrylic acid in 60 parts of deionized water, and then dropwise adding 80 parts of the dispersion to perform carboxyl modification, firstly ultrasonically dispersing for 30 minutes, and then rapidly stirring for 60 minutes at 90° C., adjusting the pH to 3.6, filtering, washing with water, and freeze-drying to obtain carboxyl-modified ferroferric oxide; ultrasonically dispersing 2 parts of the carboxyl-modified ferroferric oxide in 500 parts of N,N-dimethylformamide, sequentially adding 1.2 parts of EDC·HCl, 0.6 parts of N-hydroxysuccinimide and 1 part of propargylamine, stirring at room temperature overnight, washing with water, and freeze-drying to obtain terminal acetylated ferroferric oxide. (2) 4 parts of silicon dioxide were added to 60 parts of toluene and ultrasonically dispersed, and then 0.2 parts of γ-glycidyloxypropyltrimethoxysilane were added to react at 80°C for 14 hours, filtered, washed with toluene, and vacuum dried; then added to a mixture of 40 parts of methanol and 10 parts of deionized water, and then 2 parts of sodium azide and 0.01 parts of ammonium chloride were added to react at 70°C for 24 hours, washed with water, and vacuum dried; then mixed with 4 parts of terminal acetylated ferrosoferric oxide, 2 parts of sodium ascorbate, 12 parts of triethylamine, and 600 parts of N,N-dimethyl The mixture was mixed with formamide for click reaction, placed under a nitrogen atmosphere, 0.02 parts of copper sulfate pentahydrate were added and reacted at 40°C for 30 hours, washed, and dried to obtain a silica composite material; 4 parts of maleic anhydride were added to 40 parts of N,N-dimethylformamide and stirred thoroughly, and then 2 parts of the silica composite material were added for thermal reaction, placed under a nitrogen atmosphere, stirred at 100°C for 10 hours, cooled to room temperature, dissolved in trimethicone, filtered, washed with acetone, and dried in vacuo to obtain an anionic silica composite material.
[0091] Example 3
[0092] This embodiment provides a method for preparing antistatic and flame-retardant ultra-high molecular weight polyethylene fibers, which includes the following steps:
[0093] 85 parts of polyethylene (45 parts of ultra-high molecular weight polyethylene I and 40 parts of high-density polyethylene), 3 parts of cationic montmorillonite, 3 parts of anionic silica composite material, 0.7 part of antioxidant 1010, 0.9 part of lubricant N,N'-ethylenebisstearamide, and 0.5 part of compatibilizer Arkema CA100 are mixed and then added to a blender. After stirring evenly, they are put into a twin-screw extruder for melt spinning (at a temperature of 190 °C), and water bath cooling is carried out to obtain antistatic and flame-retardant ultra-high molecular weight polyethylene fibers.
[0094] Preparation of the cationic montmorillonite: By weight, 11 parts of thionyl chloride and 25 parts of dimethyl sulfoxide are mixed, and then 9 parts of methacrylic acid, 25 parts of N,N-dimethylformamide, and 45 parts of tetrahydrofuran are added for heating reaction (at a temperature of 62 °C and a time of 170 min). Then 7 parts of 2,4,6-tris(dimethylaminomethyl)phenol and 3 parts of ethylenediamine are added and reacted at 62 °C for 170 min to obtain an intermediate; 25 parts of the intermediate and 7 parts of a hydrochloric acid solution with a mass concentration of 38% are added to 45 parts of absolute ethanol. First, acidification is carried out at 25 °C for 25 min, and then 18 parts of epichlorohydrin are added for a constant temperature reaction. The pH is adjusted to 7.4, and a constant temperature reaction is carried out at 42 °C for 9 h to obtain a quaternary ammonium salt solution; 3 parts of sodium montmorillonite are added to 45 parts of the quaternary ammonium salt solution for cationic intercalation treatment, stirred at 85 °C for 26 h, filtered, washed with water, dried, and ground to obtain cationic montmorillonite.
[0095] Preparation of the anionic silica composite material: (1) Ultrasonically disperse 0.4 parts of magnetite in 90 parts of deionized water to obtain a dispersion. Ultrasonically disperse 0.3 parts of polyacrylic acid in 70 parts of deionized water, then add 90 parts of the dispersion for carboxyl modification. First, ultrasonically disperse for 35 min, then rapidly stir at 95 °C for 55 min, adjust the pH to 3.7, filter, wash with water, and freeze-dry to obtain carboxyl-modified magnetite. Ultrasonically disperse 3 parts of the carboxyl-modified magnetite in 550 parts of N,N-dimethylformamide, sequentially add 1.3 parts of EDC·HCl, 0.7 parts of N-hydroxysuccinimide, and 2 parts of propargylamine, stir at room temperature overnight, wash with water, and freeze-dry to obtain end-group alkynylated magnetite. (2) Ultrasonically disperse 6 parts of silica in 70 parts of toluene, then add 0.4 parts of γ-glycidoxypropyltrimethoxysilane and react at 85 °C for 13 h, filter by suction, wash with toluene, and dry in vacuo. Then add it to a mixed solution of 45 parts of methanol and 11 parts of deionized water, add 3 parts of sodium azide and 0.02 parts of ammonium chloride, and react at 75 °C for 22 h, wash with water, and dry in vacuo. Then mix it with 6 parts of end-group alkynylated magnetite, 3 parts of sodium ascorbate, 14 parts of triethylamine, and 700 parts of N,N-dimethylformamide for click reaction, place it in a nitrogen atmosphere, add 0.03 parts of copper sulfate pentahydrate, and react at 45 °C for 26 h, wash, and dry to obtain a silica composite material. Add 6 parts of maleic anhydride to 45 parts of N,N-dimethylformamide and stir well, then add 3 parts of the silica composite material for thermal reaction, place it in a nitrogen atmosphere, stir at 110 °C for 9 h, cool to room temperature, dissolve it in chloroform, filter, wash with acetone, and dry in vacuo to obtain the anionic silica composite material.
[0096] Example 4
[0097] The difference between this example and Example 1 is that commercially available silica (product number S433667) is used to replace the anionic silica composite material.
[0098] Comparative Example 1
[0099] The difference between this comparative example and Example 1 is that commercially available sodium-based montmorillonite (product number M916670) is used to replace the cationic montmorillonite.
[0100] Comparative Example 2
[0101] The difference between this comparative example and Example 1 is that ultra-high molecular weight polyethylene II (product number P77511) is used to replace ultra-high molecular weight polyethylene I (grade LL-GM-1080).
[0102] Comparative Example 3
[0103] The difference between this comparative example and Example 1 is that the dosage of ultra-high molecular weight polyethylene I is changed to 80 parts, and the dosage of high-density polyethylene is changed to 10 parts.
[0104] Comparative Example 4
[0105] The difference between this comparative example and Example 1 is that the dosage of ultra-high molecular weight polyethylene I is changed to 30 parts, and the dosage of high-density polyethylene is changed to 60 parts.
[0106] Test the properties of the ultra-high molecular weight polyethylene fibers provided in the above examples and comparative examples. The test methods are as follows:
[0107] (1) Antistatic performance test: Prepare textiles from ultra-high molecular weight polyethylene fibers for testing. Refer to "GB / T 12703.1-2021 Test methods for electrostatic properties of textiles - Part 1: Corona charging method", and use the half-life of static voltage to represent the antistatic performance.
[0108] (2) Flame retardant performance test: Conduct the test according to the requirements of "GB / T 5454-1997 Test method for combustion performance of textiles - Oxygen index method".
[0109] The above performance test data are shown in Table 1.
[0110] Table 1 Performance test results
[0111]
[0112]
[0113] As can be seen from the above, the present invention selects ultra-high molecular weight polyethylene with a viscosity-average molecular weight of 1,000,000 to 1,200,000, reduces the melt spinning temperature, and simultaneously introduces functional components such as cationic montmorillonite and anionic silica composites, etc., to prepare antistatic and flame retardant ultra-high molecular weight polyethylene fibers (Examples 1 to 3), whose comprehensive performance is the best, the half-life of static voltage is 1.5 to 1.8 s, and the oxygen index is 38.9 to 39.4%.
[0114] Compared with Example 1, when using commercially available silica (product number S433667) to replace the anionic silica composite material, the antistatic performance becomes worse and the oxygen index decreases (Example 4); compared with Example 1, when using commercially available sodium-based montmorillonite (product number M916670) to replace the cationic montmorillonite, the antistatic performance becomes worse and the oxygen index decreases (Comparative Example 1); compared with Example 1, when using ultra-high molecular weight polyethylene II (product number P77511) to replace ultra-high molecular weight polyethylene I (grade LL-GM-1080), since the viscosity-average molecular weight of ultra-high molecular weight polyethylene II is relatively high and insufficient melt spinning temperature easily leads to product non-uniformity, the antistatic performance becomes worse and the oxygen index decreases (Comparative Example 2); compared with Example 1, when the dosage of ultra-high molecular weight polyethylene I is changed to 80 parts and the dosage of high-density polyethylene is changed to 10 parts, due to the excessive dosage of ultra-high molecular weight polyethylene I and poor compounding effect, the antistatic performance becomes worse and the oxygen index decreases (Comparative Example 3); compared with Example 1, when the dosage of ultra-high molecular weight polyethylene I is changed to 30 parts and the dosage of high-density polyethylene is changed to 60 parts, due to the insufficient dosage of ultra-high molecular weight polyethylene I and poor compounding effect, the antistatic performance becomes worse and the oxygen index decreases (Comparative Example 4).
[0115] In summary, the present invention prepares an antistatic and flame-retardant ultra-high molecular weight polyethylene fiber by selecting ultra-high molecular weight polyethylene and high-density polyethylene for compounding and adding functional components such as cationic montmorillonite and silica. Without adding graphene materials, good antistatic performance and flame-retardant performance are obtained.
Claims
1. An antistatic and flame-retardant ultra-high molecular weight polyethylene fiber, characterized in that it comprises the following raw materials in parts by weight: 80-90 parts of polyethylene, 2-4 parts of cationic montmorillonite, 2-4 parts of silica, 0.6-0.8 parts of antioxidant, 0.8-1.2 parts of lubricant, and 0.4-0.6 parts of compatibilizer; The preparation method of the cationic montmorillonite includes: taking 2-4 parts of sodium-based montmorillonite in parts by weight and adding it to 40-50 parts of quaternary ammonium salt solution for cation intercalation treatment to obtain cationic montmorillonite.
2. The antistatic and flame-retardant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that The preparation method of the quaternary ammonium salt solution includes: taking 10-12 parts of thionyl chloride and 20-30 parts of dimethyl sulfoxide in parts by weight, mixing them, then adding 8-10 parts of methacrylic acid, 20-30 parts of N,N-dimethylformamide, and 40-50 parts of tetrahydrofuran for heating reaction, then adding 6-8 parts of 2,4,6-tris(dimethylaminomethyl)phenol for esterification reaction to obtain an intermediate; subjecting 20-30 parts of the intermediate to acidification treatment, and then adding 16-20 parts of epichlorohydrin for constant temperature reaction to obtain a quaternary ammonium salt solution.
3. The antistatic and flame-retardant ultra-high molecular weight polyethylene fiber according to claim 2, characterized in that The conditions of the esterification reaction include: adding 2-4 parts of ethylenediamine and reacting at 60-64 °C for 160-180 min; The conditions of the acidification treatment include: adding 20-30 parts of the intermediate and 6-8 parts of hydrochloric acid solution with a mass concentration of 36-40% to 40-50 parts of absolute ethanol, and acidifying at 24-28 °C for 20-30 min first.
4. The antistatic and flame-retardant ultra-high molecular weight polyethylene fiber according to claim 1, characterized in that the silica is an anionic silica composite material; The preparation method of the anionic silica composite material includes: taking 4-8 parts of silica in parts by weight, performing surface modification, then mixing it with 4-8 parts of end-group alkynylated ferric tetroxide, 2-4 parts of sodium ascorbate, 12-16 parts of triethylamine, and 600-800 parts of N,N-dimethylformamide for click reaction to obtain a silica composite material; adding 4-8 parts of maleic anhydride to 40-50 parts of N,N-dimethylformamide and stirring well, then adding 2-4 parts of the silica composite material for thermal reaction to obtain an anionic silica composite material.
5. The antistatic and flame-retardant ultra-high molecular weight polyethylene fiber according to claim 4, characterized in that The conditions for the surface modification include: adding 4 - 8 parts of silica into 60 - 80 parts of toluene and dispersing them by ultrasonic treatment, then adding 0.2 - 0.6 parts of γ - glycidoxypropyltrimethoxysilane and reacting at 80 - 90 °C for 12 - 14 h, performing suction filtration, washing with toluene, and drying in vacuum; then adding it into a mixed solution of 40 - 50 parts of methanol and 10 - 12 parts of deionized water, adding 2 - 4 parts of sodium azide and 0.01 - 0.03 parts of ammonium chloride and reacting at 70 - 80 °C for 20 - 24 h, washing with water, and drying in vacuum.
6. An antistatic and flame - retardant ultra - high molecular weight polyethylene fiber according to claim 4, wherein The preparation method of the terminal - alkynylated iron tetroxide includes: ultrasonically dispersing 0.3 - 0.6 parts of iron tetroxide in 80 - 100 parts of deionized water to obtain a dispersion, ultrasonically dispersing 0.2 - 0.4 parts of polyacrylic acid in 60 - 80 parts of deionized water, then dropping 80 - 100 parts of the dispersion for carboxyl modification to obtain carboxyl - modified iron tetroxide; performing terminal - alkynylation on the carboxyl - modified iron tetroxide to obtain terminal - alkynylated iron tetroxide.
7. An antistatic and flame - retardant ultra - high molecular weight polyethylene fiber according to claim 6, wherein The conditions for the terminal - alkynylation include: ultrasonically dispersing 2 - 4 parts of the carboxyl - modified iron tetroxide in 500 - 600 parts of N,N - dimethylformamide, sequentially adding 1.2 - 1.4 parts of EDC·HCl, 0.6 - 0.8 parts of N - hydroxysuccinimide, and 1 - 3 parts of propargylamine, stirring at room temperature overnight, washing with water, and freeze - drying.
8. An antistatic and flame - retardant ultra - high molecular weight polyethylene fiber according to claim 1, wherein The polyethylene is ultra - high molecular weight polyethylene and high - density polyethylene; The mass ratio of the ultra - high molecular weight polyethylene to the high - density polyethylene is (1 - 2):1; The viscosity - average molecular weight of the ultra - high molecular weight polyethylene is 1,000,000 - 1,500,000.
9. An antistatic and flame - retardant ultra - high molecular weight polyethylene fiber according to claim 1, wherein The antioxidant is selected from one or more of antioxidant 1010 or antioxidant 168; The lubricant is selected from one or more of calcium stearate or N,N'-ethylenebisstearamide; The compatibilizer is selected from one or more of DuPont E100, DuPont E226, or Arkema CA100.
10. A preparation method of an antistatic and flame - retardant ultra - high molecular weight polyethylene fiber according to any one of claims 1 - 9, wherein It includes the following steps: Mix 80 - 90 parts of polyethylene, 2 - 4 parts of cationic montmorillonite, 2 - 4 parts of silica, 0.6 - 0.8 parts of antioxidant, 0.8 - 1.2 parts of lubricant, and 0.4 - 0.6 parts of compatibilizer, add them into a blender, stir evenly, then put them into a twin - screw extruder for melt - spinning and water - bath cooling to obtain the antistatic and flame - retardant ultra - high molecular weight polyethylene fiber.
Citation Information
Patent Citations
Temperature-resistant composite cleaning fracturing fluid and preparation method thereof
CN108285783A
Ferroferric oxide / nano oxide hybrid wave-absorbing material and preparation method thereof
CN110724492A
Antistatic flame-retardant ultra-high molecular weight polyethylene fiber and preparation method thereof
CN118461174A
High-strength ultra-high molecular weight polyethylene melt spinning fiber and preparation method thereof
CN119162699A
Special antistatic polyethylene pipe material and preparation method thereof
CN119639098A